Save that song - Hutchinson, John N. (John Nicholas) ([Balingup, W.A. : J.N. Hutchinson], 1988)
Annotation pending.
Available from Mr J. Hutchison, Wildlife Sound Studios, Balingup, W.A. 6253.
Keywords: Hutchinson, John N; Birdsongs -- Western Australia -- Recording and reproducing -- Anecdotes; Bird watchers -- Western Australia -- Biography; Child welfare - Child / parent separation - Stolen generations; Employment - Conditions; Enterprises - Pastoral industry; Hunting - Kangaroo / Wallaby; History - Biographies - Non-Indigenous - Autobiographies; Ngarinyin / Ungarinyin people (K18) (WA SE52-01); Hunting - Lizard / goanna; Yulparija people (A67) (WA SF51-07); Dance - Ceremonial; Warrwa / Warwa people (K10) (WA SE51-07); Wunambal people (K22) (WA SD51-12); Kununurra (WA East Kimberley SD52-14); Wotjulum (WA West Kimberley SE51-07); Bandilngan / Windjana Gorge (WA West Kimberley SE51-08); Wupipi / Broome (WA West Kimberley SE51-06); Mowanjum (WA West Kimberley SE51-07); Jigalong (WA East Pilbara SF51-13); Anna Plains (WA SE51-13); Noonkanbah / Yungngora (WA West Kimberley SE51-12); Beagle Bay (WA West Kimberley SE51-02); Kalumburu (WA Drysdale East Kimberley SD52-09); Munja (WA West Kimberley SE51-07); Prince Regent River (WA West Kimberley SD51-16); Port Hedland (WA East Pilbara SF50-04); Forrest River (WA East Kimberley SD52-09, SD52-10, SD52-14)